2017
DOI: 10.15171/jpd.2018.19
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of bone density with serum parathyroid hormone in hemodialysis patients; a single center study

Abstract: Introduction: The existence of a relationship between the level of serum parathyroid hormone (PTH) and bone density can be a warning sign in hemodialysis patients. Objectives: In the studies conducted so far, the relationship between these two factors has not been specifically investigated. Hence, this study was aimed to exclusively evaluate the levels of serum PTH hormone and bone density. Patients and Methods: In this cross sectional study, 85 eligible chronic hemodialysis patients aged over 18 years old who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 10 publications
3
5
1
Order By: Relevance
“…This study showed that most of ESRD patients had significantly low BMD, including osteopenia and osteoporosis, with a percentage of 83%, 71.1% and 71.1% at the total, hip and spine, respectively. See Fig 1. This is close to the findings of previous studies [14,15,21].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This study showed that most of ESRD patients had significantly low BMD, including osteopenia and osteoporosis, with a percentage of 83%, 71.1% and 71.1% at the total, hip and spine, respectively. See Fig 1. This is close to the findings of previous studies [14,15,21].…”
Section: Discussionsupporting
confidence: 92%
“…Low BMD was found to be associated with increased total duration of dialysis, higher serum PTH level, higher serum calcium level and decreased intake of elemental calcium supplement which confirms the findings of previous studies [ 9 , 14 , 22 24 ].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Omidvar B et al, study with significant P value as 272.75±122.58, 454.16±405.49, 652.26±735.41 (0.04). 22 In present study, authors have found 37.3% cases has diabetes, 93.3% cases has hypertension and 25.5% patients has ischemic heart disease. The study by Gomez AT et al, revealed the similar finding with 30.6% has diabetes, 17.9% has hypertension and 30.6% has ischemic heart diseases.…”
Section: Resultssupporting
confidence: 49%